Calibration parameters for the probing tip of a magnetic force microscope in the field of a test current loop - Goryachev, A. V.; Popkov, A. F. (Technical physics, 2006)
The subject of discussion is calibration of the tip of a magnetic force microscope using the field of a ring-shaped current loop. To calculate the calibration parameters, the magnetic contribution from the extended tip of the probe in the field of the current loop to the rigidity of the cantilever is approximated by the contribution from a point magnetic dipole and magnetic “charge” in terms of the theoretical model adopted. Three simplified models of the conic tip (with a sharpened, blunted, and rounded top) are considered. The calculated dependences of the effective calibration parameters on the radius of the current loop are compared with experimental data. It is found that the model of a uniformly magnetized tip in the form of a blunted cone provides the best fit to the experiment. The calculation results may be helpful in simulating images obtained with a magnetic force microscope and numerically testing magnetic objects.